Evaluation of Oxidative Stress in the Development of Postpartum Endometritis and Their Prognostic Significance (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The development of postpartum endometritis is characterized by aggravated obstetric-gynecological, somatic, social anamnesis and postpartum anamnesis with a high level of proinflammatory markers. The quality assessment of the predictive ability of the models was performed by using the Nagelkerke determination coefficient R², R² for an increase in the concentration of MDA is equal to = 85.67%; and for a decrease in AOA activity - 93.52%, which proves the higher prognostic significance of the obtained regression models.